A Short Review on the Dynamic Slice Management in Software-Defined Network Virtualization - Hassan, Mohamed Khalafalla; Sayed Ariffin, Sharifah Hafizah; Syed-Yusof, Sharifah Kamila; Ghazali, Nurzal Effiyana; Obeng, Kobby Asare (Engineering, Technology & Applied Science Research, 2023)
Software-Defined Network (SDN) is a contemporary networking technology that offers enhanced network flexibility and streamlines network management processes. Virtual Software-Defined Networking (vSDN) enables the dynamic allocation and sharing of physical networking resources among several slices, each representing distinct service providers or services. Each tenant is granted autonomous control over their respective services or applications within the Virtual Network (VN). Network virtualization allows providers to deliver novel, advanced services while enhancing efficiency and dependability. Utilizing numerous virtual networks on a specific infrastructure presents difficulties in implementing effective resource allocation mechanisms to prevent congestion and resource scarcity while maintaining the Service Level Agreements (SLAs) in the vSDN. A limited body of research has focused on dynamic slice allocation in the vSDN domain. This article will briefly review dynamic resource management, focusing on slice resource dynamic allocation through SDN hypervisors. The survey outlined that very few studies have tackled the impact of dynamicity slice management in vSDN, and there are research gaps in implementing proactive and intelligent frameworks for slice management in vSDN.